2011
DOI: 10.1016/j.ecss.2010.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Trophic importance of diatoms in an intertidal Zostera noltii seagrass bed: Evidence from stable isotope and fatty acid analyses

Abstract: A current predominant paradigm emphasizes the role of epiphytic algae for invertebrates in most seagrass food webs. However, in some intertidal Zostera noltii beds, epiphyte biomass is very low compared to microphytobenthos and seagrass biomasses. We assessed the role of microphytobenthos in a temperate intertidal Z. noltii bed by combining stable isotope and fatty acid (FA) analyses on primary producers, composite sources-suspended particulate organic matter (SPOM) and sediment surface organic matter (SSOM)-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
57
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 76 publications
9
57
0
Order By: Relevance
“…In addition to differences in δ 15 N among plants from different sites, a clear intra-plant variation was detected, with belowground tissues showing consistently an enriched isotopic signal, by~1-2‰ with respect to leaf tissues; a similar enrichment has been observed for seagrasses in other studies (Lepoint et al, 2003;Lebreton et al, 2011). Although this can be partially explained by differences in the isotopic signal of the external DIN to which each vegetative compartment is exposed, other processes at plant physiological level may also be involved.…”
Section: Differences In Din Uptake Kinetics Among Sitessupporting
confidence: 56%
“…In addition to differences in δ 15 N among plants from different sites, a clear intra-plant variation was detected, with belowground tissues showing consistently an enriched isotopic signal, by~1-2‰ with respect to leaf tissues; a similar enrichment has been observed for seagrasses in other studies (Lepoint et al, 2003;Lebreton et al, 2011). Although this can be partially explained by differences in the isotopic signal of the external DIN to which each vegetative compartment is exposed, other processes at plant physiological level may also be involved.…”
Section: Differences In Din Uptake Kinetics Among Sitessupporting
confidence: 56%
“…On the other side, the low percentages of bacterial FAs and LCFAs (2.02%) and FA 6:0 (mean < 0.5%) suggest that detritus of M. spicatum was partially utilized via bacteria mediation, which corroborates the previous study of Lebreton et al (2011). When M. spicatum decomposed, LCFAs remain unchanged in planktonic and deposition detritus for more than 4 months, or even for years, whereas PUFAs including 18:3x3 are rapidly decomposed (Mfilinge et al, 2003).…”
Section: Discussionsupporting
confidence: 82%
“…Living diatom biomarkers were highly contributed to the cichlids' diets (total mean = 16.9% of both consumers profile), whereas decaying diatom biomarker was lower contributor (mean = 3.77% of both consumers profile). These results showed that diatoms are the main trophic resource in tilapias diets due to their high biomass, constant availability and their high nutritional quality (Lebreton et al, 2011). Nevertheless fatty acid profile of epiphytic diatoms was similar to that of cichlids but it was excluded as a potential food source because the carbon signature of epiphytic diatoms (d 13 C) was much enriched (mean = À21.95‰) compared to d 13 C of cichlids (mean = À26.68‰).…”
Section: Discussionmentioning
confidence: 60%
“…Several studies during the last decade have used natural stable isotope ratios to elucidate the principal food sources of macrobenthos in seagrass beds, stressing the importance of seagrass-associated sources and/or microphytobenthos (MPB) (Lepoint et al, 2000;Kharlamenko et al, 2001;Moncreiff and Sullivan, 2001;Baeta et al, 2009;Carlier et al, 2009;Lebreton et al, 2011;Ouisse et al, 2012;Vafeiadou et al, 2013a). Less information is available for meiobenthos resource utilization in seagrass beds (Vizzini et al, 2000b(Vizzini et al, , 2002aBaeta et al, 2009;Leduc et al, 2009;Lebreton et al, 2011Lebreton et al, , 2012, with none of the studies including meiofauna at the level of feeding types, families, genera or species.…”
Section: Introductionmentioning
confidence: 99%
“…Less information is available for meiobenthos resource utilization in seagrass beds (Vizzini et al, 2000b(Vizzini et al, , 2002aBaeta et al, 2009;Leduc et al, 2009;Lebreton et al, 2011Lebreton et al, , 2012, with none of the studies including meiofauna at the level of feeding types, families, genera or species. The few studies using natural isotope abundances to unravel food resources of coastal meiofauna at this level (Carman and Fry, 2002;Moens et al, , 2005Moens et al, , 2013Rzeznik-Orignac et al, 2008) do not examine seagrass habitats.…”
Section: Introductionmentioning
confidence: 99%